Correlation of glycemic control in newborn at birth to maternal glycemic control - Edbor, Anjali; Chikkam, Kavya; Dua, Himanshu (Indian Journal of Child Health, 2020)
Background: Gestational diabetes mellitus (GDM) is a common endocrine disorder of pregnancy with an incidence of approximately 1 in 1000. Perinatal outcomes and long-term sequelae in infants of diabetic mothers (IDM) are related to onset and duration of glucose intolerance and severity of disease in mother. Objective: The objective of the study was to study the correlation of glycemic control in newborn to maternal glycemic control (glycosylated hemoglobin [HbA1c] levels). The occurrence of congenital malformations and other neonatal complications was also studied. Materials and Methods: A longitudinal study was carried out at a tertiary hospital of Central India from November 2018 to October 2019 and a total of 47 cases which were admitted during the study periodwere included in the study. All babies born either gestational or type 1 or type 2 diabetic mothers were included in the study. The sample size was calculated to be 38. Statistical analysis was done using Epi Info 7.1. Poor maternal glycemic control during the 3rd trimester has been shown to be strongly and independently correlate with neonatal hypoglycemia. Neonatal HbA1c correlates well with maternal HbA1c level after birth. Results: Poor maternal glycemic control during the 3rd trimester has been shown to be strongly and independently correlate with neonatal hypoglycemia. Neonatal HbA1c correlates well with maternal HbA1c level after birth. There was no statistically significant difference found between mean birth weight and gender (p>0.05) in IDM. Conclusion: It was concluded that IDM babies are at risk of hypoglycemia if the mother’s HbA1c level goes beyond 6.5%. There was no significant correlation between the duration of diabetes and hypoglycemia and other congenital anomalies associated with maternal diabetes.